THE IMPACT OF TEENAGE PREGNANCY ON THE HEALTH OF MOTHERS AND BABY - Theresia Mindarsih; Frida Sisternike Pay (JTH: Journal of Technology and Health, 2026)
Teenage pregnancy remains a major public health concern because it is associated with increased maternal and neonatal morbidity resulting from biological, nutritional, and psychosocial immaturity. Despite global efforts to reduce its incidence, teenage pregnancy continues to contribute to adverse pregnancy outcomes, particularly in low- and middle-income countries. This study aimed to describe the maternal and infant health outcomes associated with teenage pregnancy in the Sikumana Community Health Center working area, Kupang City, Indonesia. A retrospective descriptive survey was conducted using secondary data from maternal and delivery medical records of all teenage mothers who received antenatal care and delivered at the Sikumana Community Health Center between 2024 and 2025. A total of 67 respondents were included through total sampling, and data were analyzed descriptively using frequency distributions. Among adolescent mothers, anemia was identified in 8.95% of cases (5.97% mild, 1.49% moderate, and 1.49% severe), premature rupture of membranes in 1.49%, chronic energy deficiency in 26.87%, and cesarean section delivery in 7.46%. Regarding neonatal outcomes, 7.46% of infants were born with low birth weight and 8.96% experienced neonatal asphyxia. Most respondents were aged 16–19 years (97.01%), had completed senior high school (79.10%), were unmarried (100%), and were primigravida (100%). Teenage pregnancy is associated with adverse maternal and neonatal health outcomes, particularly chronic energy deficiency, anemia, low birth weight, and neonatal asphyxia. Strengthening adolescent reproductive health education, improving access to quality antenatal care, and implementing early identification of high-risk pregnancies are essential to reduce pregnancy-related complications and improve maternal and child health outcomes.